HUBUNGAN PERMENDAG NO.53/M-DAG/PER/8/2012, BANK, FRANCHISOR DAN UMKM - Warno, Warno (Sekolah Tinggi Ilmu Ekonomi Semarang, 2013)
From the research conducted it can be concluded as follows: SMEs welcome party when there is co-operation to take over the process and minimarket franschise The bank approved  the agreement  which  required  a  decent  home loan  to  be funded. c. Franchisor approve the agreement because it can run the Regulation could also expand its business Welcomed the government for the establishment of cooperation between the Bank, SME and franschisor